Relevance of Vocational Skill Acquisition Programmes for Employment in an Era of Dwindling Economy in Bauchi Metropolis - Idris, Abubakar; Buba, Umar; Suleiman, Lukman; Adamu, Adamu Ladan (American Economic & Social Review, 2017)
The study was conducted to find out the relevance of vocational skill acquisition programmes for employment in an era of dwindling economy in Bauchi metropolis. Two research questions were formulated for the study. An 11 items questionnaire was developed and used to get responses from the trainees. A descriptive survey was employed for the study. The questionnaire was validated by two experts from Vocational and Technology Education Department. Mean statistical tool was used to analyze the data collected. The result of the study indicated that the most important objectives of vocational skill acquisition programmes were to enable youth to acquire vocational skills that would provide gainful employment as well as raise their standards of living. Also the trainees perceived the relevance of skill acquisition programmesas centers for imparting marketable skills that focus more on practical aspect than theory. It was recommended that training courses should be relevant to the need of the sectors and target group. Those training centers should serve as places for providing employment opportunities to the public since our economy is declining and government opportunities are less because of scarce resources.